Secure Authentication Scheme for Medicine Anti-Counterfeiting System in IoT Environment - Wazid, Mohammad; Das, Ashok Kumar; Khan, Muhammad Khurram; Al-Ghaiheb, Abdulatif Al-Dhawailie; Kumar, Neeraj; Vasilakos, Athanasios V. (IEEE internet of things journal, 2017)
A counterfeit drug is a medication or pharmaceutical product which is manufactured and made available on the market to deceptively represent its origin, authenticity and effectiveness, etc., and causes serious threats to the health of a patient. Counterfeited medicines have an adverse effect on the public health and cause revenue loss to the legitimate manufacturing organizations. In this paper, we propose a new authentication scheme for medicine anticounterfeiting system in the Internet of Things environment which is used for checking the authenticity of pharmaceutical products (dosage forms). The proposed scheme utilizes the near field communication (NFC) and is suitable for mobile environment, which also provides efficient NFC update phase. The security analysis using the widely accepted real-or-random model proves that the proposed scheme provides the session key security. The proposed scheme also protects other known attacks which are analyzed informally. Furthermore, the formal security verification using the broadly accepted automated validation of Internet security protocols and applications tool shows that the proposed scheme is secure. The scheme is efficient with respect to computation and communication costs, and also it provides additional functionality features when compared to other existing schemes. Finally, for demonstration of the practicality of the scheme, we evaluate it using the broadly accepted NS2 simulation.